Perimenstrual headache: Migraine without aura or premenstrual syndrome symptom? - Šundić Ana; Zidverc-Trajković Jasna; Vujović Svetlana; Šternić Nadežda (Vojnosanitetski Pregled, 2010)
Background/Aim. Definition of menstrual migraine as a specific clinical entity or, maybe, migraine headache with menstrually related occurring, still remains unresolved question. The aim of this study was to investigate if perimenstrual headache in our patients fulfills diagnostic the International Classification of Headache Disorders (ICHD) criteria for migraine without aura or represents a different type of headache which is the symptom of premenstrual syndrome (PMS). Methods. The study included 50 women with headache in perimenstrual period in at least two out of three menstrual cycles, during the last year or longer. Two questionnaires, a questionnaire for headache and a questionnaire for PMS, were used. Results. The majority of all the examined women, 29 of them, had migraine and PMS and 9 women had migraine without PMS. Headache in 38 (76.0%) patients fulfilled diagnostic criteria for menstrual migraine, (26 and 12 women had pure menstrual migraine and menstrually related migraine respectively). Intensity of PMS was not different in a groups of women with different types of headache (p = 0.184): a total number of PMS symptoms was 8.2 ± 4.6 in the group with pure menstrual migraine, 10.8 ± 3.9 in the group with menstrually related migraine and 10.8 ± 6.3 in the group with non-migraine headache. Conclusion. This study shows that headache, occuring in perimenstrual period, is not always migraine, but could fulfill criteria for tension-type headache, as well. Specific characteristics of perimenstrual headache, which could distinguish it as a symptom of PMS, were not found. Expected relation in time of headache onset and menarche was not confirmed.